The Resources for Tree Planting Platform - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The platform is online and fully available to extension workers, tree seed collectors, nursery operators and tree growers, as well as to planners of tree planting, for tree researchers and for government policy makers.